Identification of specific codon 201 mutation of the DCC Gene in the colonoscopic specimen of colorectal cancer - Serwer, Tehmina; Mohsin Wahid; Imtiaz, Fauzia; Memon, Amjad Siraj (Journal of the Pakistan Medical Association, 2024)
Objective: To identify the mutation in codon 201 of the deleted in colorectal cancer gene in colorectal cancer, and to correlate that mutation to the histopathological grading of colorectal cancer. Method: The cross-sectional study was conducted from February 2019 to February 2021 after approval from the ethics review board of the Dow University of Health Sciences, Karachi, and comprised biopsy-proven colorectal cancer patients regardless of age and gender. After histopathological reporting, formalin-fixed paraffin-embedded tissue blocks of colorectal cancer were used for deoxyribonucleic acid extraction, followed by polymerase chain reaction optimisation and deoxyribonucleic acid Sanger sequencing for mutational analysis. Data was analysed using SPSS 25. Results: Of the 100 biopsy specimens assessed, 45(45%) were selected. Of them, 13(29%) samples failed to show any band on gel electrophoresis. The remaining 32(71%) samples were used for Sanger sequencing. Of these, 1(3%) sample did not sequence, while 31(97%) showed sequencing. All the sequenced samples identified a mutation in codon 201 of exon 3 in the deleted in colorectal cancer gene; 30(97%) showed homozygosity, and 1(3%) showed heterozygosity. No significant association of point mutation was noted with various demographic and clinicopathological parameters (p>0.05). Conclusion: The deleted in colorectal cancer gene’s missense mutation in codon 201 was frequently observed in colorectal cancer patients. Key Words: Colorectal cancer, Single nucleotide polymorphism, DCC gene, Codon 201 mutation.